Manajemen Supervisi Akademik Kepala Sekolah Dalam Meningkatkan Kinerja Guru - Riska Putri Maharani; Muhammad Ghafar (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Ponorogo, 2023)
The existence of a school principal has a very important role in developing and leading educational institutions, because the principal is one of the main key holders of success in all processes and results. Therefore, the principal as the supervisor is expected to provide motivation, coaching, direction which will later be useful to increase the spirit of teacher performance. The research was conducted at SMP Negeri 1 Ponorogo which has become a favorite school in Ponorogo because of the completeness of its assets and teaching staff. This study aims to: (1) Planning for the principal's academic supervision in improving teacher performance, (2) Implementation of the principal's academic supervision in improving teacher performance, (3) Evaluation of the principal's academic supervision in improving teacher performance. This research is a case study research with a qualitative approach with data collection conducted through interviews, observation, and documentation. Based on the research conducted, it can be concluded that the principal's academic supervision planning in improving teacher performance at SMP Negeri 1 Ponorogo is carried out by holding official meetings every semester, involving educators in the planning process for implementing supervision to all teachers. The implementation of academic supervision is carried out by applying sustainable and active principles that are useful for improving the quality of education and the smooth running of activities in schools, applying individual supervision techniques and group supervision techniques to directly monitor teachers in the classroom. Evaluation of academic supervision is carried out with a meeting between the supervision team and the teacher after learning and there is a follow-up to the supervision evaluation in improving teacher performance.